Predictors of purchase intention of luxury South Sea pearls. Issue 4 (November 2016) - 't Hart, Brian; Teah, Min; Butcher, Luke
Highlights: This study aims to better understand the reasons behind a decline in sales of luxury South Sea pearls by exploring the different antecedents of consumers' purchase intention. Data were collected using a self-administered questionnaire and analysed using a combination of statistical analysis techniques. Findings showed that attitudes, novelty seeking and self-efficacy are significant predictors of purchase intention, however, interpersonal influence is not. The study shows how consumer knowledge plays a fundamental role in the development of consumers' purchase intention towards luxury South Sea pearls. This study provides industry practitioners and retailers with new insights into the pearl industry so they are able to better develop products and design branding strategies. Abstract: This study aims to gain further insight into the reasons behind the decline in sales of luxury South Sea pearls by exploring the different antecedents of consumers' purchase intention using the theory of planned behaviour. Data were collected using a self-administered questionnaire and analysed using a combination of statistical analysis techniques. Findings showed that attitudes, novelty seeking and self-efficacy are significant predictors of purchase intention, while interpersonal influences are not a significant predictor. This study provides industry practitioners, researchers, policy makers and retailers with new insights into the pearling industry so they are able to better develop products, design branding strategies and form policies which address current consumer behaviour. Chinese Abstract: 本研究旨在通过采用计划行为理论探讨消费者购买意向的不同前因, 进一步了解奢华南海珍珠销量下滑的原因。使用自填问卷收集数据并使用统计分析技术的组合进行分析。表明结果的态度、寻求新颖性和自我效能是购买意向的重要预测因素, 而人际影响不是重要的预测因素。这项研究为行业从业者、研究人员、政策制定者和零售商提供了对珍珠产业的新见解, 便于他们能够更好地开发产品, 设计品牌战略并形成可应对当前消费者行为的政策。